Rheological and Tribological Properties of Seaweed Powders as Thickeners for Liquid Foods - Osorio-Lira, F (Elsevier B.V., 2024)
Thickened liquid foods are particularly interesting in culinary applications and the management of swallowing disorders. Polysaccharide molecules and suspended soft particles play a major role in increasing viscosity and mouthfeel. In this work, tribo-rheological effects of finely ground particles (less than 75 μm) of Durvillaea antarctica seaweed (SP) as a minimally processed and natural alternative to commercial thickeners were studied. Shear viscosity (η), viscoelastic moduli (G′, G″), and the coefficient of friction (CoF) were determined for SP dispersions, using as controls two commercial thickeners: modified maize starch-based (TE) and xanthan gum-based (TU). SP and SP dispersions were characterized microstructurally and evaluated at concentrations of 1.2%, 2.4%, and 4.8% w/v, with and without artificial saliva (AS). SP dispersions exhibited a pseudoplastic behavior in the range of shear rates 0.1–100 s−1 and viscoelasticity (G’>G”) in the 0.1–80 rad/s frequency range. The incorporation of AS had a dilution effect in SP and TU dispersions, but additionally, in the case of TE, a hydrolyzing effect decreased the values of the responses. In the tribology experiments, all samples followed a Stribeck curve. SP dispersions were more lubricating than AS and controls in the physiological range of velocities during oral processing and swallowing (e.g.,>100 mm/s). The thickening, viscoelastic, and lubrication behavior of SP dispersions were attributed to the soluble solids released from the SP (37%–51% d. w.) and interactions with ghosts of SP particles in the continuous aqueous phase. Fine seaweed particles may be a sustainable and low-cost alternative to commercial thickeners in some food applications. © Elsevier Ltd